2015
DOI: 10.1620/tjem.237.77
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Levels of Interleukin 35 in Patients with Rheumatoid Arthritis

Abstract: Interleukin 35 (IL-35) is a newly discovered anti-inflammatory cytokine. Recent studies have indicated that it plays a crucial role in the pathogenesis of autoimmune diseases. In humans, IL-35 is predominantly secreted from regulatory T cells. This study aimed to measure serum IL-35 levels in patients with rheumatoid arthritis (RA) and in control individuals, and analyze its association with disease indicators of RA. One hundred patients with RA were recruited, and 50 volunteers were enrolled as healthy contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
(31 reference statements)
5
21
1
Order By: Relevance
“…Based on its immunological functions, IL-35 has been studied in the context of many autoimmune diseases. For instance, patients with RA (Ning et al 2015) or idiopathic thrombocytopenic purpura (Yang et al 2014b) showed below-normal serum concentrations of IL-35. In RA, IL-35 was negatively related to the concentration of rheumatoid factor and percentage of neutrophils (Ning et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on its immunological functions, IL-35 has been studied in the context of many autoimmune diseases. For instance, patients with RA (Ning et al 2015) or idiopathic thrombocytopenic purpura (Yang et al 2014b) showed below-normal serum concentrations of IL-35. In RA, IL-35 was negatively related to the concentration of rheumatoid factor and percentage of neutrophils (Ning et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, patients with RA (Ning et al 2015) or idiopathic thrombocytopenic purpura (Yang et al 2014b) showed below-normal serum concentrations of IL-35. In RA, IL-35 was negatively related to the concentration of rheumatoid factor and percentage of neutrophils (Ning et al 2015). In idiopathic thrombocytopenia purpura, IL-35 concentration was positively correlated with the numbers of circulating platelets and Tregs, but negatively correlated with the number of Th1 cells (Yang et al 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the role of IL-35 in autoimmune diseases; in a mouse model, Niedbala et al (16) revealed that recombinant IL-35 effectively attenuated collagen-induced arthritis, and a subsequent study by Kochetkova et al (17) reported similar results. Several clinical studies indicated that serum IL-35 levels were significantly lower in patients with RA; furthermore, treatment with IL-35 suppressed inflammatory cytokine levels and enhanced the regulatory function of Tregs (18,19). However, few studies have analyzed the number and function of Tregs in patients with RA.…”
Section: Introductionmentioning
confidence: 99%
“…IL‐35 is a recently discovered member of the IL‐12 cytokine family consisting of Epstein‐Barr‐virus‐induced gene 3 (Ebi3) and IL‐12α subunits . Unlike other members of this cytokine family, IL‐35 exhibits only immunosuppressive properties and has been shown to mediate protection in several diseases in both humans and mouse models . IL‐35 is secreted by and contributes to the suppressor function of Foxp3 + Treg .…”
Section: Introductionmentioning
confidence: 99%